Perovskite thin film prepared by low-pressure vacuum gas phase, solar cell and method

By stepping the solid-gas reaction between the ammonium halide salt and the inorganic precursor under low-pressure vacuum conditions, the problem of ammonium halide salt easy to decompose when the perovskite film is prepared under high temperature and high vacuum conditions is solved, and the preparation and industrial production of high-quality perovskite films are achieved.

CN119562742APending Publication Date: 2025-03-04WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411619298.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When existing perovskite solar cells are prepared under high temperature and high vacuum conditions, the ammonium halide salt is prone to decomposition, resulting in poor film quality, poor repeatability and large-area unevenness.

Method used

The low-pressure vacuum air phase preparation method is used to deposit inorganic precursors on the substrate by physical gas phase method, and gasify the ammonium halide salt in stages under low vacuum conditions to carry out continuous solid-gas reactions to form a high-quality perovskite film.

Benefits of technology

It maintains the integrity of the ammonium halide salt structure, improves the component uniformity, product yield and repeatability of perovskite films, simplifies the production process, reduces material waste, and broadens the production methods of photovoltaic building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562742A_ABST
    Figure CN119562742A_ABST
Patent Text Reader

Abstract

The invention relates to a perovskite thin film prepared by a low-pressure vacuum vapor phase, a solar cell and a method. The method comprises the following steps: S1, depositing an inorganic precursor on a charge transport layer of a substrate by using a physical vapor phase method; s2, gasifying the first ammonium halide salt under a low vacuum condition and diffusing the gasified first ammonium halide salt into the inorganic precursor to form a first perovskite thin film; and / or S3, gasifying the second ammonium halide salt under a low vacuum condition and diffusing the gasified second ammonium halide salt into the first perovskite thin film to form a second perovskite thin film; and / or S4, gasifying the third ammonium halide salt under a low vacuum condition and diffusing the gasified third ammonium halide salt into the second perovskite thin film to form a third perovskite thin film; wherein at least one of the step S2, the step S3 and the step S4 is selected. According to the method, continuous solid-gas reaction is carried out on the ammonium halide salt gasified step by step and the inorganic precursor, cross contamination of an organic source is reduced, the utilization rate of an organic material is increased, and the obtained perovskite thin film is uniform in component, high in product yield and good in repeatability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new photovoltaic materials, and in particular to a low-pressure vacuum vapor-phase prepared perovskite film, a solar cell and a method. Background Art

[0002] Photovoltaic power generation is one of the key technologies for providing green energy. Its ultra-large-scale social application depends on further efficiency improvement and cost reduction, that is, further improvement of power generation efficiency and further reduction of power generation cost. Perovskite solar cells (PSCs) use artificially synthesized organic-inorganic hybrid perovskites as photoelectric conversion materials. It is a thin-film photovoltaic power generation technology with the characteristics of low material usage, adjustable color, and high power generation efficiency. However, at present, PSCs mainly use wet processes, that is, the battery materials and solvents are mixed into inks, and then prepared by spin coating, coating, printing and other technical methods. This process not only has problems such as difficulty in enlarging the battery area, but also in the wet process, the drying process from wet film to dry film is affected by the environment, resulting in low battery performance yield. In addition, environmental safety issues such as the volatilization and treatment of organic solvents in wet film preparation will significantly increase production costs.

[0003] The vacuum process itself has the advantages of high repeatability and no need to introduce solvents, which can solve various problems in the above-mentioned wet process. However, the vacuum process of perovskite is usually carried out under high vacuum by multi-source co-evaporation or continuous thermal evaporation, which usually requires high vacuum (~10 -3 Under conditions of high temperature and high vacuum, one of the components of perovskite, ammonium halide, is converted into gaseous state through physical gas phase, thereby reacting with another component, lead iodide, to form perovskite material. However, under high temperature and high vacuum conditions, ammonium halide is easy to decompose, resulting in poor quality of perovskite film, poor repeatability, and uneven film over a large area. Therefore, the preparation of high-quality perovskite film under low vacuum (>1 Pa) conditions is a difficulty in the application industry. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned technical deficiencies and provide a low-pressure vacuum vapor-phase prepared perovskite film, solar cell and method, so as to solve the technical problems of low film yield and poor repeatability caused by the easy decomposition of raw material ammonium halide under high temperature and high vacuum conditions when preparing perovskite film in the prior art.

[0005] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a method for preparing a perovskite film in a low-pressure vacuum phase, comprising the following steps: S1, depositing an inorganic precursor on a charge transport layer of a substrate by a physical vapor method; S2, vaporizing a first ammonium halide salt under low vacuum conditions and diffusing it into the inorganic precursor to form a first perovskite film; and / or, S3, vaporizing a second ammonium halide salt under low vacuum conditions and diffusing it into the first perovskite film to form a second perovskite film; and / or, S4, vaporizing a third ammonium halide salt under low vacuum conditions and diffusing it into the second perovskite film to form a third perovskite film; wherein at least one of step S2, step S3 and step S4 is selected.

[0006] In a second aspect, the present invention provides a perovskite film produced by the above method.

[0007] In a third aspect, the present invention provides a solar cell comprising an electrode, a first charge transport layer, a perovskite layer, a second charge transport layer and a back electrode, wherein the perovskite layer is the above-mentioned perovskite film.

[0008] Compared with the prior art, the beneficial effects of the present invention include: The present invention maintains the integrity of the ammonium halide structure by performing continuous solid-gas reaction with an inorganic precursor by step-by-step gasification under low pressure, and realizes continuous close-range volatilization gas phase growth of perovskite; at the same time, the present invention gasifies the ammonium halide in steps, maintains the single stability of the organic source component, and reduces the cross contamination of the organic source; avoids the problem of non-reusability caused by inconsistent gasification rates in mixed organic sources, improves the utilization rate of organic materials, and thus prepares a high-quality perovskite film with uniform components, high product yield, and good repeatability. Therefore, the perovskite film of the present invention adopts a fully industrialized vacuum process preparation, simplifies the production process, and the ammonium halide source can be reused, reducing material waste, broadening the production method of photovoltaic building materials, and is conducive to cost reduction and efficiency improvement. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 It is a schematic diagram of the structure of a three-source close-range volatilization gas phase device; Figure 2 It is a schematic diagram of the partial structure of a three-source close-range volatilization gas phase device; Figure 1 and Figure 2 In the figure, 1-inlet chamber; 2-organic source chamber; 3-transition chamber; 4-sample outlet chamber; 5-transmission device; 6-pressure regulating valve; 7-pressure sensor; 8-stage; 9-liftable baffle; 21-first organic source chamber; 22-second organic source chamber; 23-third organic source chamber; 201-substrate carrier; 202-organic source carrier; Figure 3This is a box diagram of the efficiency of the pin-type perovskite semi-transparent battery prepared by continuous low-pressure vacuum vapor phase reaction at different times in Example 1; Figure 4 This is a box diagram of the efficiency of a pin-type perovskite semi-transparent cell prepared under different vacuum conditions using a continuous low-pressure vacuum vapor reaction in Example 2; Figure 5 This is the efficiency diagram of the NIP type continuous low-pressure vacuum vapor-phase prepared perovskite cell prepared in Example 3; Figure 6 This is the IV efficiency diagram of the pin-type continuous low-pressure vacuum vapor-phase prepared perovskite solar module prepared in Example 4; Figure 7 This is the IV efficiency diagram of the NIP-type continuous low-pressure vacuum vapor-phase prepared perovskite solar module prepared in Example 5; Figure 8 This is the efficiency diagram of the pin-type continuous low-pressure vacuum vapor-phase prepared perovskite cell prepared in Example 6; Fig. 9 1 is a box plot of the efficiency of three different batches of batteries prepared continuously in Comparative Example 1 and Example 2. DETAILED DESCRIPTION

[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0011] Abbreviation Explanation Me-2PACz: (2-(3,6-dimethyl-9H-carbazol-9-yl)ethyl)phosphonic acid, molecular formula C 16 H 18 NO3P; 2PACz: (2-(9H-carbazol-9-yl)ethyl)phosphonic acid, molecular formula: C 14 H 14 NO3P; 4PACz: [4-(9H-carbazol-9-yl)butyl]phosphonic acid, molecular formula: C 16 H 18 NO3P; FACl: formamidine chloride; FABr: formamidine bromide; FAI: formamidine iodide; spiro-TTB: 2,2',7,7'-tetrakis(di-p-tolylamino)spiro-9,9'-bifluorene; ITO: Indium Tin Oxide; IZO: Indium zinc oxide; IZrO: zirconium-doped indium oxide; IWO: Indium oxide doped tungsten oxide; ALD: Atomic layer deposition.

[0012] It has been reported that perovskite solar cells are mainly prepared using a wet process, which not only has a low yield and is not conducive to large-scale industrial production, but also produces a large amount of waste VOC emissions, causing environmental pollution. Although the vacuum process itself has advantages such as high repeatability and no need to introduce solvents, the traditional perovskite vacuum process needs to be carried out under high temperature and high vacuum conditions. One of the components of perovskite, ammonium halide, is easily decomposed under high temperature and high vacuum conditions, which leads to problems such as poor quality of the resulting perovskite film, poor repeatability, and uneven large-area film.

[0013] In order to increase the consistency and repeatability of the film and reduce the preparation cost, the present invention provides a low-pressure vacuum vapor-phase prepared perovskite film, solar cell and method. The method realizes continuous close-range volatilization vapor phase growth of perovskite by continuous solid-gas reaction of ammonium halide salts that are step-vaporized at low pressure with solid lead halide films, thereby preparing high-quality perovskite films, which are fully compatible with industrial production.

[0014] In a first aspect, the present invention provides a method for preparing a perovskite thin film in a low-pressure vacuum phase, comprising the following steps: S1, depositing an inorganic precursor on a charge transport layer of a substrate by a physical vapor method; S2, vaporizing the first ammonium halide salt under low vacuum conditions and diffusing it into the inorganic precursor to form a first perovskite film; and / or, S3, vaporizing the second ammonium halide salt under low vacuum conditions and diffusing it into the first perovskite film to form a second perovskite film; and / or, S4, vaporizing the third ammonium halide salt under low vacuum conditions and diffusing it into the second perovskite film to form a third perovskite film; Among them, at least one step is selected from step S2, step S3 and step S4; preferably two or three steps are selected.

[0015] It should be noted that the volatility of the first ammonium halide salt, the second ammonium halide salt and the third ammonium halide salt in the present invention ranges from easy to difficult. If two of them are selected, they can be the first ammonium halide salt and the second ammonium halide salt, the second ammonium halide salt and the third ammonium halide salt, or the first ammonium halide salt and the third ammonium halide salt.

[0016] Preferably, in step S1, the charge transport layer is an n-type semiconductor material or a p-type small molecule self-assembled molecular layer.

[0017] Further preferably, the n-type semiconductor material includes tin dioxide or titanium dioxide; and the p-type small molecule self-assembled molecular layer includes Me-2PACz, 2PACz or 4PACz.

[0018] Preferably, in step S1, the inorganic precursor includes any two or three combinations of CsX and PbY2; wherein X is any one of I, Br and Cl, and Y is any one of I, Br and Cl; in the physical vapor method, the evaporation rate of CsX is 0.1-0.5 A / s, and the thickness is 20-60 nm; the evaporation rate of PbY2 is 1-5 A / s, and the thickness is 200-600 nm.

[0019] Preferably, in step S2, the first ammonium halide is formamidine chloride (FACl), the source temperature is 110-130°C, the reaction pressure is 5-100 Pa, and the reaction time is 2-15 min.

[0020] Preferably, in step S3, the second ammonium halide salt is formamidine bromide (FABr), the source temperature is 140-160° C., the reaction pressure is 5-100 Pa, and the reaction time is 2-15 min.

[0021] Preferably, in step S4, the third ammonium halide salt is formamidine iodide (FAI), the source temperature is 160-180° C., the reaction pressure is 5-100 Pa, and the reaction time is 2-15 min.

[0022] Preferably, the perovskite film is prepared in a three-source close-range volatilization gas phase apparatus, which is a continuous low-pressure vacuum gas phase apparatus; see Figure 1 and Figure 2 The three-source close-range volatile gas phase device includes a sample injection chamber 1, an organic source chamber 2, a transition chamber 3, a sample output chamber 4, a transmission device 5 and a stage 8, wherein the organic source chamber 2 includes a first organic source chamber 21, a second organic source chamber 22 and a third organic source chamber 23, the first organic source chamber 21 is connected to the sample injection chamber 1, and a transition chamber 3 is arranged between the first organic source chamber 21 and the second organic source chamber 22 and between the second organic source chamber 22 and the third organic source chamber 23; the third organic source chamber 23 is connected to the sample output chamber 4.

[0023] The stage 8 is horizontally moved to different working steps in the sample injection chamber 1, the organic source chamber 2, the transition chamber 3 and the sample output chamber 4 through the transmission device 5; the stage 8 can adopt an ultra-precision Z-axis translation table, on which a substrate carrier stage 201 is arranged, and the substrate carrier stage 201 is used to place a substrate with a precursor; the transmission device 5 can adopt a chain drive, and many structures can be used to realize the transmission, which is not specifically limited here.

[0024] An organic source stage 202 is provided in the organic source chamber 2 for placing the organic source. A high-precision substrate lifting platform is provided between the stage 8 and the substrate stage 201, and the height of the substrate stage 201 can be adjusted by the high-precision substrate lifting platform to control the reaction distance between the substrate with the precursor and the organic source (i.e., ammonium halide) to be 100-500 μm.

[0025] In the organic source chamber, the organic source used is an organic target prepared by the tablet pressing method or a dense organic film pre-deposited on a glass substrate by ultrasonic spraying. Specifically, the organic target prepared by the tablet pressing method is obtained by grinding the ammonium halide salt into powder and mixing it evenly with the molecular sieve. The volume ratio of the ammonium halide salt to the molecular sieve is 1: (0.8-1.2) to obtain a mixed powder, which is pressed into an organic target by a tablet press at a temperature above 50 °C and a pressure above 200 MPa. The dense organic film prepared by ultrasonic spraying is directly sprayed with ammonium halide salt. The spraying pressure is 0.2 MPa, the spraying speed is 20 cm / min, and the total load on the substrate is 20 mg / cm 2 .

[0026] It can be understood that the sample inlet chamber 1, the transition chamber 3 and the sample outlet chamber 4 are all provided with chamber doors, liftable baffles 9, heating platforms, pressure regulating valves 6 and pressure sensors 7, wherein the liftable baffles 9 are raised to connect the two chambers, and the liftable baffles 9 are lowered to form independent sealed chambers; the organic source chamber 2 is provided with chamber doors, heating platforms, pressure regulating valves 6, pressure sensors 7, organic source wafer stages 202, and organic source baffles, and the organic source baffles are movable. When the substrate is in the preheating state, the organic source baffles can be closed to prevent the organic source from entering the substrate in advance; the chamber door can be a lifting sealed door. The heat source is provided by the heating platform, and the pressure in each chamber is monitored by the pressure sensor 7. The pressure regulating valve 6 is connected to an external vacuum pump to form a pressure regulating device.

[0027] Preferably, the sources arranged in the three-source chamber are sequentially transitioned from volatile sources to less volatile sources; the temperature required for volatilization from volatile sources to less volatile sources will gradually increase, allowing the sample to transition from low temperature to high temperature; and different types of ammonium salts can be set, and different anions can be introduced to customize the perovskite band gap, and the type of ammonium salt can be changed or adjusted according to the actual demand for perovskite.

[0028] In a second aspect, the present invention provides a perovskite film produced by the above method.

[0029] In a third aspect, the present invention provides a solar cell comprising an electrode, a first charge transport layer, a perovskite layer, a second charge transport layer and a back electrode.

[0030] Preferably, the perovskite photovoltaic device comprises a pin-type solar cell or a nip-type solar cell.

[0031] Further preferably, the method for preparing a PIN type solar cell specifically comprises: S1. Physical vapor deposition of a 3-8 nm self-assembled molecular layer on the substrate at an evaporation rate of 0.1-0.2 A / s, annealing at 100 °C in air for 10 min to form a p-type charge transport layer (i.e., hole transport layer); S2. Using physical vapor deposition of any two or three of the perovskite inorganic precursors CsX and PbY2 on the p-type charge transport layer; S3. Then, under low vacuum conditions, the ammonium halide salt is vaporized and diffused into the inorganic precursor to form Cs x FA( 1-x )Pb(I y Br 1-y-z Cl z )3 perovskite film; wherein the precursor and the ammonium halide source are always kept at an ultra-close distance of 100 to 500 μm; S4. Thermally evaporate 15-30 nm electron transport film C60 on the perovskite film at an evaporation rate of 0.1-0.2 A / s; then use atomic layer deposition (ALD) to prepare 10-40 nm SnO2 as a double electron layer and play a certain blocking role, and the growth rate of ALDSnO2 is 0.1-0.15 nm / cycle; optionally, an interface modification film can also be deposited on the tin oxide; S5. Finally, the top transparent electrode is deposited in two steps: first, 20 nm is deposited at 30-40 W, and then 80-100 nm is deposited at 75-90 W. The target material is any one of ITO, IZO, IZrO or IWO.

[0032] Further preferably, the method for preparing the NIP type solar cell specifically comprises: S1. Prepare SnO2 electron transport film on substrate by RF power magnetron sputtering or atomic layer deposition. The power of RF power magnetron sputtering SnO2 is 35-90 W, and the thickness is 10-40 nm. The growth rate of ALDSnO2 is 0.3-0.7 nm / cycle, and the thickness is 10-40 nm, forming an n-type charge transport layer (i.e., electron transport layer). S2. Using physical vapor deposition of any two or three of the perovskite inorganic precursors CsX and PbY2 on the n-type charge transport layer; S3. Then, under low vacuum conditions, the ammonium halide salt is vaporized and diffused into the inorganic precursor to form Cs x FA( 1-x )Pb(I y Br 1-y-z Cl z)3 perovskite film; wherein the precursor and the ammonium halide source are always kept at an ultra-close distance of 100 to 500 μm; S4. Physical vapor deposition of spiro-TTB on the perovskite film at an evaporation rate of 0.1-0.2 A / s and a thickness of 10-20 nm to obtain a hole transport film; S5. Thermally evaporate 5-15 nm molybdenum oxide on the hole transport film as a film to prevent magnetron damage, with a physical vapor rate of 0.1-0.2 A / s; S6. Finally, the top transparent electrode is deposited in two steps: first, 20 nm is deposited at 30-40 W, and then 80-100 nm is deposited at 75-90 W. The target material is any one of ITO, IZO, IZrO or IWO.

[0033] The main working process of the present invention is: The inorganic precursor is deposited on the charge (carrier) transport layer by a physical vapor phase method, and the inorganic precursor is passed through the injection chamber into an ultra-close-range volatilization gas phase device, and then the first ammonium halide is vaporized at low temperature and low pressure, and diffused into the inorganic precursor to form a first perovskite film; then it is transferred into a chamber containing a second ammonium halide source, and the second ammonium halide is vaporized at low temperature and pressure, and diffused into the first perovskite film to form a second perovskite film; finally, it is transferred into a chamber containing a third ammonium halide source, and the third ammonium halide is vaporized at low temperature and low pressure, and diffused into the second perovskite film to form the final perovskite film. Among them, the precursor and the ammonium halide source are always kept at an ultra-close distance.

[0034] The mechanism of action and advantages of the present invention are: (1) Reduce the waste of ammonium halide materials. The present invention provides a method for preparing perovskite thin films by a continuous close-range volatilization gas phase method. The inorganic precursor film gradually reacts with the vaporized ammonium halide (organic ammonium salt) under low vacuum and low temperature, thereby maintaining the integrity of the ammonium halide structure. By vaporizing the ammonium halide in steps, the organic source components are kept single and stable, reducing cross-contamination of the organic source. The problem of non-reusability in mixed organic sources due to inconsistent vaporization rates is avoided, thereby improving the utilization rate of organic materials.

[0035] (2) Provide a perovskite film production device. The present invention provides a perovskite photovoltaic film production device that is fully compatible with industrial full vacuum production. The generated perovskite has uniform components throughout the longitudinal direction, which simplifies the production process of perovskite cells, improves the yield of cell performance, and helps promote the industrialization of thin-film photovoltaic building materials.

[0036] (3) Meeting architectural aesthetic requirements. The present invention provides a thin-film photovoltaic device prepared by a fully industrialized process. The perovskite light-absorbing film can be designed according to the requirements of photovoltaic buildings. The color of the light-absorbing layer can be precisely controlled by changing the chemical composition of the precursor and the ammonium halide salt. The light-absorbing film pattern can also be customized in the production process to meet the basic requirements of architectural aesthetics.

[0037] Therefore, the perovskite film of the present invention is prepared by a fully industrialized vacuum process, which simplifies the production process. The ammonium halide source can be reused to reduce material waste. It can not only improve the utilization rate of organic salts, broaden the production types of perovskite batteries, and reduce production costs, but also solve technical problems such as the difficulty of industrial production of perovskite photovoltaic building materials, which is conducive to promotion to other photovoltaic device fields. In addition, the color and pattern can be customized, which can not only meet the basic aesthetic requirements of the building, but also reduce the production cost of perovskite photovoltaic building materials.

[0038] The present invention is described in detail below with reference to specific embodiments.

[0039] Example 1 A method for continuously preparing a perovskite thin film and a solar cell (pin type) in a low-pressure vacuum phase, comprising the following steps: (1) 5 nm MeO-2PACz was thermally evaporated on a conductive glass substrate and annealed at 100 °C for 10 min to form a hole transport layer.

[0040] (2) Physical vapor deposition of perovskite inorganic precursors CsBr and PbI2 was performed on MeO-2PACz. 30 mg CsBr was weighed and placed in an evaporation boat with an evaporation rate of 0.3 A / s and a thickness of 35 nm. 500 mg PbI2 was weighed and placed in an evaporation boat with an evaporation rate of 3 A / s and a thickness of 350 nm.

[0041] (3) The inorganic precursor is passed through the injection chamber into the ultra-close volatilization gas phase device, and then FACl is vaporized at a source temperature of 120 °C and a reaction pressure of 100 Pa, and diffused into the inorganic precursor for a reaction of 5 min; it is then transferred into a chamber equipped with a FAI source at a source temperature of 170 °C and a reaction pressure of 100 Pa for a reaction of 5 min to form the final Cs x FA( 1-x )Pb(I y Br 1-z-y Cl z )3 perovskite film. The distance between the precursor and the ammonium halide source is always kept at an ultra-close distance of 100, 200, 300, 400, and 500 μm.

[0042] (4) A 20 nm thick electron transport film C60 was thermally evaporated on the perovskite film. Then, 15 nm SnO2 was deposited by ALD with a growth rate of 0.12 nm / cycle.

[0043] (5) The final preparation area is 0.25 cm 2 The 100 nm indium tin oxide top transparent electrode was first deposited with 20 nm using 35 W power and then 80 nm using 80 W power.

[0044] The effective area of ​​the resulting solar cell is 0.16 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, the photoelectric conversion efficiency is tested under one sun. The results are as follows Figure 3 It shows that as the distance between the precursor and the ammonium halide source increases, the battery efficiency tends to increase first and then decrease; if the distance is too close, the reaction speed will be very fast, and it is easy to over-react to generate impurities, reducing the device efficiency; if the distance is too far, the reaction will be slower, and it is easy to react incompletely in the same time, increasing the time cost; therefore, the distance between the precursor and the ammonium halide source is preferably 100-500 μm, more preferably 300 μm, at which the average efficiency is the highest.

[0045] Example 2 A solar cell (pin type), the preparation steps are basically the same as those in Example 1, the distance between the precursor and the ammonium halide is maintained at 300 μm, the difference is that the reaction pressure in step (3) is 5, 50, 100, and 300 Pa respectively.

[0046] The active area of ​​the cell is 0.16 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, the photoelectric conversion efficiency is tested under one sun. The results are as follows Figure 4 It is shown that when the gas phase reaction pressure is 300 Pa, the pressure in the chamber is too low, and the volatilization power of the organic ammonium salt source is insufficient, which will cause incomplete gas phase reaction and reduce device performance. The effect is similar when the vacuum degree of the close-range volatilization gas phase reaction is 5-100 Pa, indicating that the present invention can form high-quality perovskite batteries under low pressure and low vacuum conditions.

[0047] And when the reaction pressure in Example 2 is 100 Pa ( Figure 4 100 Pa), the distance between the precursor and the ammonium halide salt is maintained at 300 μm ( Figure 3 The conditions of 300 μm in the middle are the same. Figure 3 and Figure 4 By comparison, the test results of the photoelectric conversion efficiency of the two groups of batteries are similar, which shows that the present invention has good repeatability, the prepared batteries have high stability, and are conducive to mass production.

[0048] Example 3 A method for continuously preparing perovskite solar cells (NIP type) in a low-pressure vacuum phase, the steps are as follows: (1) Atomic layer deposition was used to grow 30 nm tin oxide on the substrate at a growth rate of 0.5 nm / cycle and annealed at 180 °C for 30 min to obtain an electron transport layer. (2) Physical vapor deposition of perovskite inorganic precursors CsBr and PbI2 was used on the electron transport film. 30 mg of CsBr was weighed and placed in an evaporation boat with an evaporation rate of 0.3 A / s and a thickness of 35 nm. 500 mg of PbI2 was weighed and placed in an evaporation boat with an evaporation rate of 3 A / s and a thickness of 350 nm.

[0049] (3) The inorganic precursor is passed through the injection chamber into the ultra-close volatilization gas phase device, and then FACl is vaporized at a source temperature of 120 °C and a reaction pressure of 50 Pa, and diffused into the inorganic precursor for a reaction of 3 min; it is then transferred into a chamber equipped with a FAI source at a source temperature of 170 °C and a reaction pressure of 50 Pa for a reaction of 3 min to form the final Cs x FA( 1-x )Pb(I y Br 1-z-y Cl z )3 perovskite film. The precursor and the ammonium halide source are always kept at an ultra-close distance of 300 μm.

[0050] (4) 15 nm spiro-TTB was physically vapor deposited on the perovskite film as a hole transport film.

[0051] (5) 9 nm molybdenum oxide was thermally evaporated on spiro-TTB as a barrier film.

[0052] (6) Finally, a two-step deposition method was used to prepare a 100 nm indium tin oxide top transparent electrode. First, 20 nm was deposited using 35 W power, and then 80 nm was deposited using 80 W power.

[0053] The resulting solar cell has an effective area of ​​1 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, the photoelectric conversion efficiency is tested under one sun. The results are as follows Figure 5 As shown in Figure 2, the cell reverse scanning photoelectric conversion efficiency is 17.4%, with an open circuit voltage of 1.01 V and a short circuit current density of 23.1 mA·cm -2, the fill factor is 0.74; the forward scanning photoelectric conversion efficiency of the battery is 17.0%, with an open circuit voltage of 0.98 V and a short circuit current density of 23.1 mA·cm -2 , the filling factor is 0.75.

[0054] Example 4 A method for continuously preparing a modular perovskite solar cell (pin type) in a low-pressure vacuum phase, the steps are as follows: (1) Place 5×5 cm 2 The conductive glass substrate was cut with an 80 W laser P1 line to divide the substrate into 6 sub-cells. 5 nm MeO-2PACz was thermally evaporated on nickel oxide at 0.1-0.2 A / s and annealed at 100 °C for 10 min.

[0055] (2) Physical vapor deposition of perovskite inorganic precursors CsBr and PbI2 was performed on MeO-2PACz. 30 mg CsBr was weighed and placed in an evaporation boat with an evaporation rate of 0.3 A / s and a thickness of 35 nm. 500 mg PbI2 was weighed and placed in an evaporation boat with an evaporation rate of 3 A / s and a thickness of 350 nm.

[0056] (3) The inorganic precursor is passed through the injection chamber into the ultra-close volatilization gas phase device, and then FACl is vaporized at a source temperature of 120 °C and a reaction pressure of 50 Pa, diffused into the inorganic precursor, and reacted for 5 min; it is then transferred into a chamber equipped with a FAI source at a source temperature of 170 °C and a reaction pressure of 50 Pa, and reacted for 5 min to form the final Cs x FA( 1-x )Pb(I y Br 1-x-y Cl z )3 perovskite film. The precursor and the ammonium halide source are always kept at an ultra-close distance of 300 μm.

[0057] (4) A 20 nm electron transport layer C60 was thermally evaporated on the perovskite film using 0.1-0.2 A / s. Then 15 nm SnO2 was deposited using ALD with a growth rate of 0.12 nm / cycle to obtain an electron transport film.

[0058] (5) Use a 36 W laser to cut out the P2 line (all layers on the conductive glass are cut off).

[0059] (6) Finally, a two-step deposition method was used to prepare a 100 nm indium tin oxide top transparent electrode. First, 20 nm was deposited using 35 W power, and then 80 nm was deposited using 80 W power.

[0060] (7) Use a mask to evaporate a 100 nm thick silver grid line on the indium tin oxide. Use a laser to cut out the P3 line and divide the battery into 6 series-connected batteries.

[0061] The effective area of ​​the resulting module-type perovskite solar cell is 10 cm 2 , the simulated sunlight intensity is 100 mWcm -2 , that is, the photoelectric conversion efficiency is tested under one sun. The results are as follows Figure 6 The results show that the reverse scanning photoelectric conversion efficiency of the battery is 15.1%, with an open circuit voltage of 5.59 V, a short circuit current of 38.5 mA, and a fill factor of 0.70, indicating the scalability of the present invention.

[0062] Example 5 A method for continuously preparing a modular perovskite solar cell (nip type) in a low-pressure vacuum phase, the steps are as follows: (1) Place 5×5 cm 2 The conductive glass substrate was cut with an 80 W laser P1 line to divide the substrate into 6 sub-cells. A 30 nm tin oxide layer was grown by atomic layer deposition at a growth rate of 0.5 nm / cycle and annealed at 180 °C for 30 min to obtain an electron transport layer.

[0063] (2) Physical vapor deposition of perovskite inorganic precursors CsBr and PbI2 was used on the electron transport layer. 30 mg CsBr was weighed and placed in an evaporation boat with an evaporation rate of 0.3 A / s and a thickness of 35 nm. 500 mg PbI2 was weighed and placed in an evaporation boat with an evaporation rate of 3 A / s and a thickness of 350 nm.

[0064] (3) The inorganic precursor is passed through the injection chamber into the ultra-close volatilization gas phase device, and then FACl is vaporized at a source temperature of 120 °C and a reaction pressure of 50 Pa, and diffused into the inorganic precursor for a reaction of 3 min; it is then transferred into a chamber containing FABr at a source temperature of 150 °C and a reaction pressure of 50 Pa for a reaction of 3 min, and finally transferred into a chamber containing a FAI source at a source temperature of 170 °C and a reaction pressure of 50 Pa for a reaction of 3 min to form the final Cs x FA (1-x) Pb(I y Br 1-y-z Cl z )3 perovskite film. The precursor and the ammonium halide source are always kept at an ultra-close distance of 300 μm.

[0065] (4) 15 nm of spiro-TTB was physically vapor deposited on the perovskite film at an evaporation rate of 0.1-0.2 A / s to obtain an electron transport layer.

[0066] (5) 9 nm MoO was thermally evaporated on spiro-TTB as a barrier layer at a physical vapor rate of 0.1-0.2 A / s.

[0067] (6) Cut out the P2 line using a 36 W laser.

[0068] (7) Finally, prepare a 100 nm indium tin oxide top transparent electrode by first depositing 20 nm at 35 W and then 80 nm at 80 W.

[0069] (8) Use a mask to evaporate a 100 nm thick silver grid line on the indium tin oxide. Use a laser to cut out the P3 line and divide the battery into 6 series-connected batteries.

[0070] The effective area of ​​the resulting module-type perovskite solar cell is 10 cm 2 , the simulated sunlight intensity is 100 mWcm -2 , that is, the photoelectric conversion efficiency is tested under one sun. The results are as follows Figure 7 It shows that the battery reverse scan photoelectric conversion efficiency is 15.0%, with an open circuit voltage of 5.81 V, a short circuit current of 38.6 mA, and a fill factor of 0.67.

[0071] Example 6 A solar cell (pin type), the preparation steps are basically the same as those in Example 1, except that step (3) is specifically as follows: The inorganic precursor is passed through the injection chamber into the ultra-close volatilization gas phase device, and then the FACl is vaporized at a source temperature of 120 °C and a reaction pressure of 100 Pa, and diffused into the inorganic precursor for 5 min; then it is transferred to a chamber equipped with FABr, the source temperature is 150 °C, the reaction pressure is 50 Pa, and the reaction is carried out for 5 min. Finally, it is transferred to a chamber equipped with a FAI source, the source temperature is 170 °C, the reaction pressure is 100 Pa, and the reaction is carried out for 5 min to form the final Cs x FA (1-x) Pb(I y Br 1-y-z Cl z )3Perovskite film.

[0072] The active area of ​​the battery is 1 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, the photoelectric conversion efficiency is tested under one sun. The results are as follows Figure 8The reverse scanning photoelectric conversion efficiency of the battery is 16.4%, with an open circuit voltage of 1.11 V and a short circuit current density of 21.1 mA·cm -2 , the fill factor is 0.70, the forward scan photoelectric conversion efficiency of the battery is 15.2%, the open circuit voltage is 1.09 V, and the short circuit current density is 20.9 mAcm -2 , and the filling factor is 0.66. This indicates that the present invention can control the perovskite components by controlling the organic ammonium salt, and can obtain high-efficiency batteries with flexibility.

[0073] Comparative Example 1 The difference from Example 2 is that the inorganic precursor is passed through the injection chamber into the ultra-close-range volatilization gas phase device, a mixed source of FAI:FACl = 4:0.5 (molar mass ratio) is placed at the No. 1 source position, and then the reaction pressure is 50 Pa and the reaction time is 5 min to form the final Cs x FA( 1-x )Pb(I y Br 1-y-z Cl z )3 perovskite film. The precursor and the ammonium halide source are always kept at an ultra-close distance of 300 μm. The other steps are exactly the same.

[0074] Three batches of batteries were continuously reacted using the mixed source of Comparative Example 1, and compared with three batches of batteries continuously prepared under continuous low-pressure vacuum conditions at 50 Pa using the samples of Example 2.

[0075] The effective area of ​​the resulting solar cell is 0.16 cm 2 , the simulated sunlight intensity is 100 mW cm -2 , that is, to test the photoelectric conversion efficiency under one sun. Battery data such as Fig. 9 It shows that the battery batch prepared by the continuous technology of Example 2 has a higher yield and better source reusability.

[0076] In summary, the present invention provides a low-pressure vacuum vapor-phase prepared perovskite film, solar cell and method. The low-pressure synthesis of the perovskite film adopts an assembly-line fully industrialized process, which simplifies the industrial process, reduces the waste rate of ammonium halide materials, and is conducive to promoting the commercialization of perovskite batteries.

[0077] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a perovskite thin film in a low-pressure vacuum phase, characterized in that: The following steps are involved: S1, depositing an inorganic precursor on a charge transport layer of a substrate by a physical vapor method; S2, vaporizing the first ammonium halide salt under low vacuum conditions and diffusing it into the inorganic precursor to form a first perovskite film; and / or, S3, vaporizing the second ammonium halide salt under low vacuum conditions and diffusing it into the first perovskite film to form a second perovskite film; and / or, S4, vaporizing the third ammonium halide salt under low vacuum conditions and diffusing it into the second perovskite film to form a third perovskite film; Among them, at least one step is selected from step S2, step S3 and step S4.

2. The method for preparing a perovskite thin film in a low-pressure vacuum phase according to claim 1, characterized in that: In step S1, the charge transport layer is an n-type semiconductor material or a p-type small molecule self-assembled molecular layer; In step S1, the inorganic precursor includes any two or three combinations of CsX and PbY2; wherein X is any one of I, Br and Cl, and Y is any one of I, Br and Cl; in the physical vapor method, the evaporation rate of CsX is 0.1-0.5 A / s, and the thickness is 20-60 nm; the evaporation rate of PbY2 is 1-5 A / s, and the thickness is 200-600 nm.

3. The method for preparing perovskite thin film in low pressure vacuum phase according to claim 1, characterized in that: In step S2, the first ammonium halide salt is formamidine chloride, the source temperature is 110-130°C, the reaction pressure is 5-100 Pa, and the reaction time is 2-15 min.

4. The method for preparing a perovskite thin film in a low-pressure vacuum vapor phase according to claim 1, characterized in that: In step S3, the second ammonium halide salt is formamidine bromide, the source temperature is 140-160° C., the reaction pressure is 5-100 Pa, and the reaction time is 2-15 min.

5. The method for preparing perovskite thin film in low pressure vacuum phase according to claim 1, characterized in that: In step S4, the third ammonium halide salt is formamidine iodide, the source temperature is 160-180° C., the reaction pressure is 5-100 Pa, and the reaction time is 2-15 min.

6. The method for preparing a perovskite thin film in a low-pressure vacuum vapor phase according to claim 1, characterized in that: The perovskite film is prepared in a three-source close-range volatilization gas phase device; the three-source close-range volatilization gas phase device comprises a transmission device, a stage, and a sample inlet chamber, an organic source chamber and a sample outlet chamber connected in sequence; The organic source chambers include three, and transition chambers are arranged between the organic source chambers; The stage moves horizontally in the sample inlet chamber, the organic source chamber, the transition chamber and the sample outlet chamber through a transmission device; The object stage is connected to the substrate stage through a lifting platform; an organic source stage for placing the organic source is provided in each organic source chamber.

7. The method for preparing a perovskite thin film in a low-pressure vacuum vapor phase according to claim 6, characterized in that: The organic source chamber is provided with a movable organic source baffle for separating the organic source and the substrate; The organic source is an organic target material prepared by a tablet pressing method using an ammonium halide salt or a dense organic film pre-deposited on a glass substrate using an ultrasonic spray method using an ammonium halide salt.

8. The method for preparing perovskite thin film in low pressure vacuum vapor phase according to claim 1, characterized in that: In step S2 to step S4, the reaction distance between the ammonium halide salt and the substrate is 100-500 μm.

9. A perovskite film obtained by the method according to any one of claims 1 to 8.

10. A solar cell, characterized in that: It comprises an electrode, a first charge transport layer, a perovskite layer, a second charge transport layer and a back electrode, wherein the perovskite layer is the perovskite film according to claim 9.